Irrigated area mapping using AVHRR, MODIS and LANDSAT ETM+ data for the Krishna River Basin, India - Gumma, Murali K.; Thenkabail, Prasad S.; Gautam, N.C.; Gangadhara Rao, Parthasaradhi; Velpuri, Naga Manohar (2008)
Net irrigated area in the Krishna river basin is varying quiet frequently due to water scarcity. Accurate area and extent of irrigated area in the Krishna River Basin is not available. State Irrigation Department projects large area under irrigation in the Krishna River Basin, which is attributed to its prestigious irrigation projects. However, the irrigation projects do not fulfill the demand in the basin consequently the tail Enders grow dry crops. Remote sensing replaces costly and tedious data collection on the ground, which is non-destructive. The aim of the present study is to prepare a comprehensive land use/land cover (LU/LC) map using continuous time-series data of multiple resolutions. A methodology is developed to map irrigated area categories using LANDSAT ETM+ along with coarse resolution time series imagery from AVHRR and MODIS, SRTM elevation, and other secondary data. Major stress was towards discrimination of ground-water irrigated area from surface-water irrigated area, determining of cropping patterns in irrigated area using MODIS NDVI time- series, and use of non-traditional methods of accuracy assessment using, ancillary datasets like SRTM-DEM, precipitation and state census statistics. A regression of the 9 class areas against agricultural census data explained 73% and 74% of the variance in groundwater and surface water irrigated area, respectively.